2022
DOI: 10.34172/joddd.2022.032
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of an acrylic resin containing curcumin nanoparticles: An in vitro study

Abstract: Background. Microbial accumulation is still a significant problem with removable acrylic appliances. This study aimed to assess the antimicrobial properties of a self-cured acrylic resin containing curcumin nanoparticles (CNPs). Methods. This in vitro study used 48 acrylic discs containing 0.5%, 1%, and 2% CNPs. The antimicrobial properties of the discs against Streptococcus mutans, Streptococcus sanguinis, Lactobacillus acidophilus, and Candida albicans were evaluated using disc agar diffusion (DAD), eluted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…According to their results, none of the curcumin nanoparticle concentrations showed growth inhibition zones for any microorganisms. However, all the concentrations were effective against all four microorganisms in the biofilm inhibition test except 0.5% for L. acidophilus [37].…”
Section: Antimicrobial Resultsmentioning
confidence: 94%
“…According to their results, none of the curcumin nanoparticle concentrations showed growth inhibition zones for any microorganisms. However, all the concentrations were effective against all four microorganisms in the biofilm inhibition test except 0.5% for L. acidophilus [37].…”
Section: Antimicrobial Resultsmentioning
confidence: 94%
“…Curcumin has been successfully added into acrylic resin in different concentrations as an anti-fungal agent against Candida albicans in many studies. 11,14 Although these studies proved the biological efficacy, addition of any agent in the acrylic resin may bring change in the mechanical properties due to which its use for intraoral function may not be acceptable. As there are limited studies regarding the strength of acrylic resin with curcumin incorporated as an anti-fungal additive, this study was done to evaluate the flexural strength of acrylic resin incorporated with different curcumin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Among the organic products, a study showed that incorporating 0.5%, 1% and 2% Curcumin into acrylic resin was effective against the Candida albicans, reducing their growth. 11 A denture in an intraoral environment is subjected to a variety of forces during use, which can result in flexural and impact stresses which causes it to break because acrylic resin has less flexural strength. 12 Moreover, any additive to the acrylic resin may impact the mechanical properties reducing their flexural strength.…”
Section: Introductionmentioning
confidence: 99%